Impact of COVID-19 on Anxiety, Stress, and Coping Styles in Nurses in Emergency Departments and Fever Clinics: A Cross-Sectional Survey - Cui S; Jiang Y; Shi Q; Zhang L; Kong D; Qian M; Chu J (Dove Medical Press, 2021)
Shasha Cui,1,* Yujun Jiang,2,* Qianyu Shi,1,* Lei Zhang,3 Dehua Kong,4 Meijuan Qian,1 Jing Chu3 1Department of Nursing, Nantong Health College of Jiangsu Province, Nantong City, Jiangsu Province, People’s Republic of China; 2Department of Gynecology, The Affiliated Hospital of Qingdao University, Qingdao City, Shandong Province, People’s Republic of China; 3Department of Nursing, Navy Medical University, Shanghai, People’s Republic of China; 4Department of Nursing, The 940th Hospital of Joint Logistics Support Force of Chinese People’s Liberation Army, Lanzhou City, Gansu Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing ChuDepartment of Nursing, Navy Medical University, 800 Xiang Yin Road, Shanghai, 200433, People’s Republic of ChinaTel +86-21-8187 1483Email chujing1999@smmu.edu.cnMeijuan QianDepartment of Nursing, Nantong Health College of Jiangsu Province, 288 Zhen Xing Dong Road, Nantong City, Jiangsu Province, People’s Republic of ChinaEmail 158142474@qq.comBackground: During the Coronavirus Disease 2019 (COVID-19) pandemic, emergency departments and fever clinics nurses acted as gatekeepers to the health care system. To manage the psychological problems that these nurses experience, we should develop appropriate training and intervention programs.Objective: To identify the impact of COVID-19 on the psychology of Chinese nurses in emergency departments and fever clinics and to identify associated factors.Methods: This online cross-sectional study recruited participants through snowball sampling between 13 February and 20 February 2020. Nurses self-administered the online questionnaires, including a general information questionnaire, the Self-Rating Anxiety Scale, the Perceived Stress Scale-14, and the Simplified Coping Style Questionnaire.Results: We obtained 481 responses, of which 453 were valid, an effective response rate of 94.18%. Participants who had the following characteristics had more mental health problems: female gender, fear of infection among family members, regretting being a nurse, less rest time, more night shifts, having children, lack of confidence in fighting transmission, not having emergency protection training, and negative professional attitude.Conclusion: Effective measures are necessary to preserve mental health of nurses in emergency departments and fever clinics. These include strengthening protective training, reducing night shifts, ensuring adequate rest time, and timely updating the latest pandemic situation.Keywords: COVID-19, nurses, psychological health, mental health, stress, anxiety